A Holistic Career Guidance and Counseling Model to Improve Career Decision-Making Ability of Senior High School Students (International Journal of Scientific Research and Management (IJSRM), 2025)
This study aims to develop a career guidance and counseling model for senior high school students using the research and development (R&D) approach as proposed by Sugiyono (2016), which includes nine steps: identifying potential problems, data collection, product design, design validation, design revision, product testing, product revision, application testing, and final product revision. The outcome of this research is a Holistic Career Guidance and Counseling Model consisting of seven stages: (1) rapport building and commitment, along with evaluation; (2) counselee characteristic assessment and evaluation; (3) career planning and evaluation; (4) career decision-making and evaluation; (5) career realization and evaluation; (6) comprehensive evaluation; and (7) follow-up and continued evaluation. The results of the effectiveness test indicate that the holistic model significantly improves students’ ability to make informed career decisions.